Design optimization of a lightweight rocker–bogie rover for ocean worlds applications. (11th November 2019) - Nayar, Hari; Kim, Junggon; Chamberlain-Simon, Brendan; Carpenter, Kalind; Hans, Michael; Boettcher, Anna; Meirion-Griffith, Gareth; Wilcox, Brian; Bittner, Brian
Relatively recent discoveries have shown that large quantities of water can be found on moons of some of the planets among the gas giants in our solar system. Robotic mobility systems can study the varied geology and origins of these bodies if they are able to navigate the complex terrains of ocean worlds. The topographical features of ocean worlds present a unique combination of challenges for mobility. These include cryogenic ice, penitentes, salt evaporites, chaotic regions, and regolith with uncertain shear and sinkage properties. Uncertainty in both terrain properties and geometry motivates design of a platform that is mobile within a large range of obstacle geometries and terrain properties. This article reports on a research effort to study the requirements and numerically optimize the kinematic parameters of the rover to satisfy these goals. The platforms selected in the process were further verified via simulation. A simulation and analysis of grousers generated suitable designs for interaction with similar ledges and rough terrain. From this analysis, a prototype was developed and tested to meet the wide range of topography and terramechanics conditions expected on these bodies.